Principles of selecting the syntactic structures with a figurative meaning to develop a tool for assessing cognitive functions - Yu.V. Laykova (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this article, the criteria for selecting such linguistic materials that can be used to identify the most common figurative units of the Russian language are suggested. They can be helpful in developing a tool to assess the cognitive functions in patients with diabetic encephalopathy, which is often associated with cognitive impairment. The latter is an important interdisciplinary problem. To solve it at the early stages of the disease, a successful diagnostic tool is needed. Here, paremiological units (syntactic structures with a figurative meaning) are considered as suitable candidates for this tool. The selection criteria were elaborated from G.P. Permyakov's paremiological minimum and the core part of E.E. Ivanov's paremiological corpus: a total of 123 paremiological units were identified and taken as the basis of the experiment.